Complementary and alternative medicine use by pediatric oncology patients before, during, and after treatment - Lüthi, Emmanuelle (BMC Complement Med Ther, 2021)
BACKGROUND: The prevalence of complementary and alternative medicine (CAM) use and the modalities used by pediatric oncology patients vary widely across studies. In addition, the changes in the use of CAM over the course of treatment are understudied. Thus, this study aimed to explore (1) CAM use by pediatric oncology patients in relation to specific time intervals and (2) communication about CAM use between parents and oncologists. METHODS: This retrospective cross-sectional study was conducted among parents of children diagnosed with cancer at a Swiss pediatric hematology-oncology center by means of an online questionnaire. Questions were related to their child’s CAM use over different time intervals, sources of information about CAM use, and communication with the oncologists. RESULTS: Among 140 respondents, CAM was used by 54.3% of patients before diagnosis and 69.3% of patients after diagnosis. During each defined time interval, between 50 and 58.8% of the patients used at least one CAM. Homeopathy was the most popular CAM modality used during oncology treatment, during the first year after treatment, and between 1 and 5 years after the end of treatment. Osteopathy was the most popular CAM ≥5 years after the end of oncology treatment. Forty percent of respondents did not discuss CAM with their oncologist. CONCLUSIONS: The high prevalence of CAM use and the different trends of use during the oncology care pathway and afterward underline the need to increase communication about CAM in the pediatric oncology setting, notably regarding benefits and risks of interaction with oncology treatment. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12906-021-03271-9.